Impact of implementation of Nusantara Module Activities Independent Student Exchange Program Universitas 17 Agustus 1945 Surabaya - Jatmiko, Dheny; Wahyudi, Eddy; Seputro, Harjo; Andriawan, Aris Heri; Ariyanto, Eko April; Khasanah, Umul (Technium Social Sciences Journal, 2022)
This type of research uses a quantitative approach. The quantitative approach is the approach used in research by measuring the indicators of the research variables in order to obtain an overview between these variables. Quantitative research is used to examine the population or sample. Data is collected using instruments or measuring instruments, then analyzed statistically or quantitatively. The Universitas 17 Agustus 1945 Surabaya runs the Independent Student Exchange program by accepting 32 inbound students and sending outbound students as many as 167 students throughout Indonesia outside Java, where the archipelago module is a compulsory subject offered by the Ministry of Education and Research and Technology. In this activity, there were several recipient universities that only provided online learning, so students couldn’t directly explore the knowledge gained during the PMM program. However, this doesn’t dampen the enthusiasm of students to continue learning about the diversity that exists in Indonesia.